The Dangers of Dispersal of Responsibilities - Adriana Schiopoiu Burlea; Joop Remmé (Amfiteatru Economic)
Taking into account that it is in the nature of the modern corporation that risks are distributed over several agents, we discuss in this paper the organisational behaviour as it results from such dispersal of responsibilities for both the principal and the agent. We explore the hypothesis that dispersal of responsibilities could be the result or a cause of a lack of consensus between the principal and the agent. Our findings suggest that a dispersal of responsibilities has a negative impact on the principal-agent relationship and that it represents a foundation for theoretical and empirical approaches to organisational behaviour. We find that agent perceptions of a dispersal of responsibilities are linked to his/her resistance to the principal’s interests, but this relationship is deeper than was suggested by previous research. However, if the sharing of responsibilities does not run parallel to that, we may have as a result what we call an agency problem.